A Century of Changes in the Policy of Fiscal Support for Agriculture under the Leadership of the Communist Party of China: Based on a historical institutionalism perspective - Li, Haiyan (International Journal of Global Economics and Management, 2024)
Financial support for agriculture is an important policy decision of the Communist Party of China to consistently support agricultural development. Based on historical institutionalism, looking at the evolution of the policy of fiscal support for agriculture over the past hundred years since the founding of the party, each stage can be roughly divided into: from "rent reduction and interest reduction" during the war, "scissors difference" after the founding of the People’s Republic of China to absorb agricultural resources, to diversification of financial investment, the implementation of "more giving, less taking, and revitalization" for agriculture, and high-quality development in the new era. In the new journey of comprehensively advancing the · strategy of rural revitalization, the future fiscal policy of supporting agriculture should continue to adhere to the leadership of the Communist Party of China, attach importance to the government’s policy traction and the role of the market in resource allocation, actively respond to the demands of people’s livelihood, enhance the endogenous development momentum and capacity of rural areas, and promote the good order change of the fiscal policy of supporting agriculture.